From discovery to surgery: A case report on an extremely rare coronaro-cava fistula - F. Bouriche; S. Yvorra; V. Gariboldi (Heliyon)
Coronary fistula are rare and of various anatomic or clinical presentations. We report the case of a patient presenting a coronaro-cava fistula from its discovery to the surgery.